Bankers’ demographic characteristics and their perception on the risk of asset misappropriation: Malaysian evidence / Anuar Nawawi, Mohamad Afzhan Khan Mohamad Khalil and Nurmazilah Mahzan - Nawawi, Anuar; Mohamad Khalil, Mohamad Afzhan Khan; Mahzan, Nurmazilah (2017)
Fraud has been a world-wide problem for many years and it affects not only the victims, but also companies in a very broad spectrum. The purpose of this study is to develop a reliable and valid construct for risk of asset misappropriation and to assess the association between bankers’ demographic factors and their perception on the risk of asset misappropriation. The fraud triangle theory that underlies this paper states that asset misappropriation is committed by individual due to three factors viz. opportunity, pressure, and rationalisation. Interviews and pilot study was conducted after constructing the research instrument to ensure validity of the measurement. The survey questionnaires were administered to 553 bankers out of which 334 were usable responses. This is a cross sectional study conducted on personnel of eight financial institutions in Malaysia in the year 2013. A final list of eleven items was found to be conclusive after testing for confirmatory factor analysis (chi square = 4.47; GFI = 0.93; CFI = 0.97; NFI = 0.96; TLI = 0.95; RMSEA = 0.10). Subsequently, a one-way ANOVA was employed to test for significant associations between the bankers’ demographic characteristics and their perception on the risk of asset misappropriation. It was found that bankers’ age (p = 0.01), working experience (p = 0.01), marital status (p = 0.01) and academic qualification (p = 0.10) had significant bearings on their perceptions of the risk of asset misappropriation within the financial institutions. This study recommends that the banking organizations focuses on improving its internal control system and communicate code of ethics to reduce the possibility of misconducts. Future research should focus on qualitative methodology and an in-depth review on fraud cases in Malaysia should be studied to provide more information to reduce the risk of losses in the banking sector.